Chomsky language, mind, and politics - McGilvray, James A. (James Alasdair) 1942- (Key contemporary thinkers, 2014)
Noam Chomsky is one of the most influential figures in contemporary intellectual life, known for his groundbreaking contributions to a range of fields from linguistics to political theory. This is a fully revised and updated edition of James McGilvray's highly successful introduction to Chomsky's work and thought.